Regenerated mortar and preparation and recycling method of recycled mortar

By optimizing the ratio and mixing method of the recycled mortar, the problem of low strength when the recycled powder content is high is solved, the preparation of recycled mortar with high strength and stability is achieved, the activator compounding process is simplified and the production cost and energy consumption.

CN116217156BActive Publication Date: 2025-01-21SHANGHAI CONSTR BUILDING MATERIALS TECH GRP CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202211705693.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-29
Publication Date
2025-01-21
Estimated Expiration
2042-12-29

AI Technical Summary

Technical Problem

In the prior art, the product strength is low when the amount of recycled powder is high, and the exciter takes a long time to dissolve in water. The exciter components are many and the amount range is large. It is difficult to determine the compound ratio, resulting in the product strength of the recycled powder. Stablize.

Method used

By determining the optimal ratio of cement, recycled sand powder, and activator in the recycled mortar, and using specific stirring and dissolving methods, we ensure that the activator is completely dissolved and improve the strength and stability of the recycled mortar.

Benefits of technology

It achieves high strength and stability of recycled mortar under high recycled powder content, simplifies the activator compounding process, and reduces production costs and energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116217156B_ABST
    Figure CN116217156B_ABST
Patent Text Reader

Abstract

The present invention provides a regenerated mortar and a preparation and recycling method of the regenerated mortar, and the preparation method of the regenerated mortar comprises the following steps: step 1, determining the ratio of cement, regenerated sand powder and activator in the regenerated mortar; step 2, dry mixing cement and regenerated sand powder in a stirring pot according to the ratio in step 1; step 3, stacking the activator in layers in a beaker according to the type; step 4, while the stirring pot is in a slow stirring state, adding water to the beaker and stirring with a glass rod at the same time until the activator is completely dissolved; step 5, adding water to the stirring pot until the material adheres to the inner wall around the stirring pot and does not fall off, pouring into a test mold, standing for molding, demoulding, and natural curing. The dissolution time of sodium sulfate, sodium silicate, sodium carbonate, and sodium hydroxide stacked in sequence from top to bottom in the beaker of the present invention is shorter than that of reverse stacking, and dissolving by adding water in batches is 2 to 8 minutes faster than that of dissolving by adding water once, and the dissolution efficiency is high, and the strength of the regenerated mortar prepared is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a regenerated mortar and a preparation and recycling method of the regenerated mortar. Background Art

[0002] The production of cement produces carbon dioxide, which causes global warming, which in turn causes frequent extreme weather, melting glaciers, and species extinction. To cope with this situation, the world has proposed carbon trading, that is, others spend money, you reduce emissions, and others buy your greenhouse gas emission reduction quota at a price of $10 / ton. Emission reduction measures include using less natural raw materials and more industrial and construction waste materials, such as recycled sand powder for concrete. However, recycled sand powder mixed with cement, mortar or concrete has a side effect on strength. Previous researchers used stimulants to stimulate the recycled powder and conducted the following research:

[0003] The journal (1865(2015)12-0031-02) reported that urea, sodium oxalate, ammonium oxalate, and sodium acetate had a solubilizing effect on saturated sodium sulfate solution, which increased the solubility rate of sodium sulfate. However, it did not report what means were used to promote the solubility of sodium sulfate, that is, to accelerate the dissolution rate.

[0004] Zhang Fushun mentioned in his paper "Dissolution and Filtration of Sodium Silicate" that vitreous sodium silicate is difficult to dissolve in cold water, but can dissolve in hot water at normal pressure, but the dissolution rate is slow, and low water consumption is beneficial to the dissolution rate; when steam pressure is used to dissolve solid sodium silicate in industry, the dissolution rate of solid sodium silicate increases with the increase of pressure. However, it has not been reported what means are used to promote the dissolution of sodium silicate at room temperature and pressure.

[0005] Patent CN106045361A introduces that sodium hydroxide is used as an activator in alkali slag concrete in the form of a solution, because sodium hydroxide has a large solubility, a fast dissolution rate, and is easy to prepare into a solution. However, the heat released by sodium hydroxide due to its rapid and concentrated dissolution will accelerate the hydration rate of alkali slag cement and shorten the already insufficient construction time. Therefore, sodium hydroxide in industry needs to be dissolved and cooled before use, which increases production links and costs. If sodium hydroxide is not dissolved in advance, only a retarder can be added to the concrete, but this will significantly increase the cost. The invention uses sodium carbonate and solid sodium hydroxide as composite activators. Sodium carbonate and solid sodium hydroxide are in contact and dissolved with water at the same time, and form a slurry with the active powder material under stirring. Due to the simultaneous contact with water, sodium carbonate and sodium hydroxide form a competitive dissolution relationship, reducing the heat release of sodium hydroxide. However, if the activator is not dissolved in advance, it is easy to disperse and form dark patches on the concrete surface, reducing the enhancement effect.

[0006] Patent CN114620965A uses fly ash, slag and steel slag solid waste as main raw materials, plasticizer, corrosion inhibitor, cement and bentonite as solid additives, waste glass powder and solid alkali metal hydroxide as activators, and sodium lignin sulfonate and polyethylene glycol as rheology improvers to prepare alkali-activated cementitious materials. Among them, fly ash, slag and steel slag solid waste / plasticizer, corrosion inhibitor, cement and bentonite solid additive = 15 / 85. The invention uses waste glass and alkali metal hydroxide as alkali activators. Compared with commonly used solid alkali activators such as mixed alkali activators of sodium silicate and sodium hydroxide, since solid sodium silicate itself is more time-consuming to dissolve, the alkali activator of the invention can activate silicates or aluminosilicates in glass powder solid waste by simply adding water, so the alkali activator of the invention is easy to use and saves time; and the alkali activator of the invention does not require thermal activation, which also saves energy. However, the activator / (fly ash, slag, steel slag solid waste+plasticizer, corrosion inhibitor, cement, bentonite solid additive)=67% to 733%, the amount of activator is 7 times that of the activated material, and the activation efficiency is low.

[0007] Patent CN108395276A uses 65%-95% construction waste sand powder, 3%-20% cement, and 0.1%-5% foaming agent to produce foamed concrete with a bulk density of 500-1100kg / m3, a strength of 5-15MPa, and a thermal conductivity of ≤0.030W / (m·K). However, the recycled sand powder is ground from waste concrete and bricks to a particle size of less than 2mm, which consumes a lot of energy and produces a lot of noise.

[0008] Patent CN112723773A recycles all components of construction waste. Classify construction waste: crush construction solid waste for pretreatment; sort; crush; wash and screen to obtain recycled micro powder with a particle size of <0.15mm, recycled aggregate 4.75-20mm, used for C25-C30 concrete, and recycled sand powder 0.15-4.75mm for mortar; then activate construction waste: ultra-finely grind recycled sand powder to produce recycled glue, recycled cement and recycled powder; spray, impregnate and dry recycled aggregate with organic silicon solution and silane; add polypropylene fiber to concrete preparation. However, it requires cleaning and grinding processes, which consumes a lot of energy.

[0009] Patent CN114573315A uses 47% to 85% of ground recycled sand powder, cement, lime, gypsum, gas-generating components, and curing components, and through mixing, pouring, static stop, cutting, and curing processes, a lightweight concrete with a dry density of 480kg / m3 and a compressive strength of 3.3MPa is obtained. However, the static stop temperature is 45 to 55 degrees Celsius, the time is 3 to 5 hours, the curing temperature is 180 to 230 degrees Celsius, the time is 1 to 5 hours, and the recycled sand powder needs to be ground, which consumes a lot of energy.

[0010] Patent CN111138135A uses construction waste as the basic raw material, adds curing agent, recycled sand powder, plant fiber, and water to prepare 3D printing materials with a strength of 12.1-15.1 MPa. (Construction waste + recycled sand powder) / (Construction waste + recycled sand powder + curing agent) = 57%-63%. The particle size of the recycled sand powder is 0.21-0.75mm. However, the amount of construction solid waste (construction waste + recycled sand powder) is less than 80%, the particle size of the recycled sand powder is small, and the crushing energy consumption is high.

[0011] Patent CN112592148B uses recycled sand powder, high-grade territories, calcium magnesium aluminosilicate, lime Ca(OH)2, sodium water glass, chemical additives, mineral mixed materials, coarse and fine aggregates and other raw materials, and adopts processes such as mixing, vibration compaction, casting and molding, and room temperature moisture maintenance for more than 20 days to produce a structural material with a compressive strength of 34.6 to 66.6 MPa. Among them, the recycled sand powder / (recycled sand powder+high-grade territories, calcium magnesium aluminosilicate) = 76% to 90%, and the activators lime and sodium water glass account for 6.9% to 21.4% of the mass of the recycled sand powder. However, calcium magnesium aluminosilicate is obtained by calcining raw materials mainly containing oxides of silicon, aluminum, calcium and magnesium at 1300-1550°C and then quenching with water. It belongs to magnesite cement (mainly magnesium oxysulfate cement and magnesium oxychloride cement) and special high-strength cement, and its strength can easily reach 62.5MPa; it has high cost; the heat released during hardening (1000-1350J / gMgO) is 3-4 times the hydration heat of ordinary silicate cement (300-400J / g cement), and it cannot be used simultaneously with alkaline activators such as NaOH; sticky moisture stains are prone to appear on the surface of the product when it is damp; the strength loss rate of the hardened body after long-term contact with water is 60%-80%. Moreover, sodium water glass, i.e., sodium silicate aqueous solution, is obtained by calcining quartz powder and soda ash at 1400°C to generate molten sodium silicate, quenching with water into particles, and dissolving in high-temperature and high-pressure water; it is viscous and bulky, which is not conducive to actual construction applications.

[0012] Patent CN103253882A feeds construction waste into a grinding device and grinds it repeatedly to produce recycled sand powder with a size of less than 5 mm. It states that "it is unnecessary to separate the powder from the mixed material of construction waste recycled sand powder and mix it back when using it." It points out that the recycled sand powder can be used as the main material of cement-based blocks, auxiliary materials for mortar and concrete, and cement admixtures. However, it does not introduce measures to enhance the recycled sand powder.

[0013] Patent CN110563424A uses 30% to 40% silicate cement, 30% to 40% original ash waste, 10% to 15% raw gypsum, 8% to 15% carbide slag waste, 1% to 3% glass fiber, and 5% to 15% activator to prepare a curing agent, and applies it to soft soil. When using it, the components in the curing agent are added with water and stirred, and then added to the soft soil. After stirring, compacting, molding, and maintenance, the cured soft soil has an unconfined compressive strength of 2 to 3 MPa, which is 1.5 to 2.5 times that of the cured soil using pure cement as a curing agent. Among them, the original ash waste contains more than 50% of silicon dioxide and more than 30% of aluminum oxide, which is similar to fly ash. The calcium hydroxide slag waste contains 85% of calcium hydroxide and 7% to 10% of water, which is equivalent to the calcium hydroxide activator. The raw gypsum contains calcium sulfate dihydrate with a purity of more than 95%, which is equivalent to the calcium sulfate activator. The activator contains sodium silicate and calcium chloride. The curing agent is 20% to 25% of the mass of the soft soil. Therefore, cement / (cement + original ash) = 43% to 87%. The total amount of activators calcium carbide slag, raw gypsum, sodium silicate, and calcium chloride accounts for 22% to 42% of the curing agent, and the remaining components of the curing agent, cement, original ash, and fiber, account for 58% to 78% of the curing agent. Therefore, the total amount of activators calcium carbide slag, raw gypsum, sodium silicate, and calcium chloride accounts for 4.4% to 10.5% of the soft soil, and cement, original ash, and fiber account for 11.6% to 19.5% of the soft soil. Although the cement content is low, the strength of the stabilized soil is also low.

[0014] Patent CN113233808A sets up color steel plates to enclose the construction area, installs dust collectors, processes waste concrete and sintered bricks separately, crushes them to less than 40mm with a universal crusher, crushes them again with a jaw crusher, and grinds them with a ball mill for 1 hour to less than 0.16mm to obtain recycled micro powder, which is applied to C20 and C30 concrete without adding activators. It is economical and practical when applied to C50 with a NaOH dosage of 3%, and the strength is best when the NaOH dosage is 5%. Studies have shown that when the ball milling time is 2h, the strength of recycled micro powder concrete is reduced, and the recycled micro powder ball milling time is controlled at about 1h to achieve the best state. However, the recycled micro powder dosage and concrete mix ratio are not introduced, and the micro powder needs to be ground for 1h, which consumes a lot of energy.

[0015] Patent CN112479674A uses recycled micro powder, mineral powder, fly ash, river sand, crushed stone, recycled aggregate, sodium hydroxide solid, water glass, sodium carbonate, and water to prepare recycled concrete with a compressive strength of 41-47 MPa. No cement is added to the concrete. After forming, it is left to stand for 24 hours at 205 degrees Celsius, and then standardly cured for 28 days. The particle size of the recycled micro powder is less than 0.075 mm and the 45-micron square hole sieve residue is ≤45%. During the preparation, water glass, sodium hydroxide solid and water are first mixed and left to stand for 20-48 hours, and then the recycled micro powder, mineral powder, fly ash, river sand, and recycled aggregate are put into a concrete mixer for dry mixing. Finally, the water glass-NaOH-water solution and sodium carbonate that have been left to stand in advance are added to the mixer one after another. Recycled micro powder / (recycled micro powder + mineral powder + fly ash) = 14% to 67%, (sodium hydroxide + water glass + sodium carbonate) / (recycled micro powder + mineral powder + fly ash) = 2.4% to 60%, and the amount of activator is high. Changing cement burning to high-temperature curing of concrete puts higher requirements on concrete mixing plants, and its application is limited and has no promotion value. In addition, obtaining such fine recycled micro powder requires high energy consumption processes.

[0016] Patent CN111718160A first dehydrates and dries the sludge / mud, then uses construction solid waste to prepare regenerated micropowder, determines the mineral composition ratio in the regenerated micropowder, and the potential hydration activity, prepares the corresponding alkali activator and mixes it evenly with the regenerated micropowder to generate alkali-activated regenerated micropowder, mixes it evenly with an appropriate amount of dehydrated sludge / mud, solidifies the sludge / mud, and finally performs CO2 curing treatment on the alkali-activated regenerated micropowder solidified sludge / mud. The alkali activator contains sodium silicate, sodium hydroxide, calcium hydroxide, and active magnesium oxide. The mass ratio of the alkali activator to the regenerated micropowder is between 1% and 30%. However, the strength of the solidified dehydrated sludge is only 1.28 to 2.15 MPa. In addition, in the preparation process of the regenerated micropowder, the regenerated aggregate needs to be soaked in a saturated calcium hydroxide solution and then ball-milled to a particle size of ≤20 microns. The processing process is cumbersome and energy-intensive.

[0017] Patent CN111362600B crushes and separates the aggregate from the waste cement concrete to obtain waste cement stone, grinds the waste cement stone to a fineness of 500m2 / kg to obtain recycled cement; mixes the recycled cement and water at a mass ratio of 1:0.35 to obtain a fluid recycled cement mixture, and casts the recycled cement mixture to obtain an embryo; pre-cures the embryo for 12 hours in an air atmosphere with a relative humidity of 65% and a temperature of 26°C, and then places the pre-cured embryo in a pressure tank, and carbonizes and cures the embryo for 1 hour at a CO2 purity of 99.9% and a CO2 gas pressure of 0.2MPa to obtain a hardened recycled cement stone with a compressive strength of 9MPa. However, the strength is relatively low.

[0018] Patent CN114195412B mixes 35% to 55% of recycled micropowder, 40% to 60% of cement clinker powder, and 2% to 5% of gypsum powder to obtain recycled cement. The recycled cement is applied to concrete, and its 28-day compressive strength is >40MPa. The recycled micropowder does not need to be activated, the amount of recycled micropowder is large, and the prepared recycled cement has excellent performance. The technical means adopted are to grind and sort the recycled sand powder in multiple stages to obtain micropowders in five particle size intervals, and then compound the recycled micropowders in different particle size intervals, so that the micropowders with particle sizes of 0 to 5μm, 5μm to 12μm, 8μm to 19μm, 17μm to 34μm, and 34μm to 75μm in the recycled micropowder account for 3% to 8%, 6% to 13%, 13% to 25%, 8% to 18%, and 5% to 14% of the recycled cement respectively. The particle size distribution of the recycled micropowder is determined by a laser particle size analyzer. When the 28d compressive strength of recycled cement is equivalent, the total amount of recycled micropowder in five particle size ranges is increased from 25% to 48%, which is nearly doubled compared with recycled micropowder in a single particle size range. However, it is difficult to control five micro particle size ranges in industry.

[0019] In summary, the construction waste powder recycling industry has problems such as low product strength when the recycled powder dosage is high, a long time is needed to dissolve the activator used to activate the recycled powder in water, many activator components and a wide dosage range making it difficult to determine the compounding ratio, huge differences in the strength of products made from recycled powder from 1MPa to 47MPa, the recycling process of recycled raw materials requires grinding, and the maintenance process of products made from recycled powder is complicated. Summary of the invention

[0020] In view of the shortcomings of the prior art mentioned above, the purpose of the present invention is to provide a regenerated mortar and a method for preparing and recycling the regenerated mortar, so that the strength of the regenerated mortar is high when the recycled powder content is high, the activator used to activate the regenerated powder takes a short time to dissolve in water, the optimal compounding ratio of the activator can be quickly determined, the strength of the product made of the recycled powder is stable at about 20.4 to 24.2 MPa, the recycled sand powder can be directly used without treatment after leaving the construction waste plant, and the regenerated mortar can be naturally cured.

[0021] To achieve the above purposes and other related purposes,

[0022] A first aspect of the present invention provides a method for preparing regenerated mortar, comprising the following steps:

[0023] Step 1: Determine the ratio of cement, recycled sand powder and activator in the recycled mortar;

[0024] Step 2: dry mix cement and recycled sand powder in a mixing pot according to the proportion in step 1;

[0025] Step 3: According to the ratio in step 1, stack the stimulants in layers in the beaker according to their types;

[0026] Step 4: While the stirring pot is in a slow stirring state, add water to the beaker and stir with a glass rod at the same time. After the first dissolution, pour the supernatant into the stirring pot, crush the precipitate in the beaker, add water to the beaker again and stir with a glass rod at the same time. After dissolution, pour the supernatant into the stirring pot, and repeat the cycle until the activator is completely dissolved;

[0027] Step 5: Add water to the mixing pot until the material sticks to the inner wall around the mixing pot and does not fall off, pour it into a test mold, let it stand for forming, demoulding, and natural curing.

[0028] Preferably, the step 1 specifically includes the following steps:

[0029] S1. Preliminarily determine the weight percentage range of regenerated sand powder: (regenerated sand powder + cement) is (A-30)% to A%, and the weight percentage range of activator: regenerated sand powder is 0 to (B*100)%;

[0030] S2, select the weight percentage of regenerated sand powder: (regenerated sand powder + cement) is A%, (A-10)%, (A-20)%, (A-30)%, the amount of activator is 0, prepare test blocks, measure the 7d strength, and determine the weight percentage of regenerated sand powder: (regenerated sand powder + cement) is C% according to the measurement results, C = A or (A-10) or (A-20) or (A-30);

[0031] S3. Based on C%, the activators sodium sulfate, sodium silicate, sodium carbonate and sodium hydroxide were tested respectively. The test blocks were prepared with the weight percentage of activator: regenerated sand powder B%, (B*10)% and (B*100)%, and the 7d strength was measured. According to the measurement results, the four activators were ranked according to the excitation intensity. The activator with the highest excitation intensity was recorded as Max, the activator with the second highest excitation intensity was recorded as Maxmi, the activator with the second lowest excitation intensity was recorded as Minmi, and the activator with the lowest excitation intensity was recorded as The activator is recorded as Min, the optimal weight percentage of Max and the regenerated sand powder is D%~E%, the optimal weight percentage of Maxmi and the regenerated sand powder is F%~G%, the optimal weight percentage of Minmi and the regenerated sand powder is H%~I%, the optimal weight percentage of Min and the regenerated sand powder is J%~K%, D%~E%, F%~G%, H%~I%, J%~K%=[0~B%] or [B%~(B*10)%] or [(B*10)%~(B*100)%];

[0032] S4. Based on C%, according to the dosage of Max being (E / 10)*4% of the weight of the regenerated sand powder and (E / 10)*7% of the weight of the regenerated sand powder, the dosage of Maxmi being (G / 10)*4% of the weight of the regenerated sand powder and (G / 10)*7% of the weight of the regenerated sand powder, the dosage of Minmi being (I / 10)*4% of the weight of the regenerated sand powder and (I / 10)*7% of the weight of the regenerated sand powder, and the dosage of Min being (K / 10)*4% of the weight of the regenerated sand powder and (K / 10)*7% of the weight of the regenerated sand powder, respectively prepare test blocks and measure the 7d strength. According to the strength measurement results, the optimal dosages of Max, Maxmi, Minmi and Min when mixed alone are L% of the weight of the regenerated sand powder, M% of the weight of the regenerated sand powder, N% of the weight of the regenerated sand powder and P% of the weight of the regenerated sand powder, respectively.

[0033] S5. Based on C%, conduct a compounding test on Max, Maxmi, Minmi, and Min; specifically:

[0034] S5-1. Conduct a composite admixture test on Max and Maxmi; according to the weight ratio of Max:Maxmi being 1:1, the total admixture is L% of the weight of the regenerated sand powder; the weight ratio of Max:Maxmi being 1:1, the total admixture is M% of the weight of the regenerated sand powder; the weight ratio of Max:Maxmi being L:M, the total admixture is L% of the weight of the regenerated sand powder; the weight ratio of Max:Maxmi being L / M, the total admixture is M% of the weight of the regenerated sand powder; the weight ratio of Max:Maxmi being L:M, the total admixture is D% of the weight of the regenerated sand powder; the weight ratio of Max:Maxmi being L:M, the total admixture is E% of the weight of the regenerated sand powder; the weight ratio of Max:Maxmi being L:M, the total admixture is F% of the weight of the regenerated sand powder; the weight ratio of Max:Maxmi being L:M, the total admixture is G% of the weight of the regenerated sand powder; prepare test blocks and measure the 7d strength;

[0035] S5-2. Conduct a composite admixture test on Max and Minmi; according to the weight ratio of Max:Minmi being 1:1, the total admixture being L% of the weight of the regenerated sand powder; the weight ratio of Max:Minmi being 1:1, the total admixture being N% of the weight of the regenerated sand powder; the weight ratio of Max:Minmi being L:N, the total admixture being L% of the weight of the regenerated sand powder; the weight ratio of Max:Minmi being L:N, the total admixture being N% of the weight of the regenerated sand powder; prepare test blocks and measure the 7d strength;

[0036] S5-3, test the compounding of Max, Maxmi and Minmi; according to the weight ratio of Max:Maxmi:Minmi is 1:1:1, the total amount is L% of the weight of the regenerated sand powder; the weight ratio of Max:Maxmi:Minmi is 1:1:1, the total amount is M% of the weight of the regenerated sand powder; the weight ratio of Max:Maxmi:Minmi is 1:1:1, the total amount is N% of the weight of the regenerated sand powder; the weight ratio of Max:Maxmi:Minmi is L:M:N, the total amount is L% of the weight of the regenerated sand powder; the weight ratio of Max:Maxmi:Minmi is L:M:N, the total amount is M% of the weight of the regenerated sand powder; the weight ratio of Max:Maxmi:Minmi is L:M:N, The total admixture is N% of the weight of the regenerated sand powder; Max:Maxmi:Minmi is L:M:N, and the total admixture is D% of the weight of the regenerated sand powder; the weight ratio of Max:Maxmi:Minmi is L:M:N, and the total admixture is E% of the weight of the regenerated sand powder; the weight ratio of Max:Maxmi:Minmi is L:M:N, and the total admixture is F% of the weight of the regenerated sand powder; the weight ratio of Max:Maxmi:Minmi is L:M:N, and the total admixture is G%; the weight ratio of Max:Maxmi:Minmi is L:M:N, and the total admixture is H% of the weight of the regenerated sand powder; the weight ratio of Max:Maxmi:Minmi is L:M:N, and the total admixture is I% of the weight of the regenerated sand powder; prepare test blocks and measure the 7d strength;

[0037] S5-4. Conduct a composite admixture test on Max, Maxmi, Minmi and Min; according to the weight ratio of Max:Maxmi:Minmi:Min of 1:1:1:1, the total admixture is L% of the weight of the regenerated sand powder; the weight ratio of Max:Maxmi:Minmi:Min is 1:1:1:1, the total admixture is M% of the weight of the regenerated sand powder; the weight ratio of Max:Maxmi:Minmi:Min is 1:1:1:1, the total admixture is N% of the weight of the regenerated sand powder; Max:Maxmi:Minmi The weight ratio of Max:Maxmi:Minmi:Min is 1:1:1:1, and the total amount is P% of the weight of the recycled sand powder; the weight ratio of Max:Maxmi:Minmi:Min is L:M:N:P, and the total amount is L% of the weight of the recycled sand powder; the weight ratio of Max:Maxmi:Minmi:Min is L:M:N:P, and the total amount is M% of the weight of the recycled sand powder; the weight ratio of Max:Maxmi:Minmi:Min is L:M:N:P, and the total amount is N% of the weight of the recycled sand powder; the weight ratio of Maxmi:Minmi:Min is The weight ratio of Maxmi:Minmi:Min is L:M:N:P, and the total amount is P% of the weight of the regenerated sand powder; the weight ratio of Maxmi:Minmi:Min is L:M:N:P, and the total amount is D% of the weight of the regenerated sand powder; the weight ratio of Maxmi:Minmi:Min is L:M:N:P, and the total amount is E% of the weight of the regenerated sand powder; the weight ratio of Maxmi:Minmi:Min is L:M:N:P, and the total amount is F% of the weight of the regenerated sand powder; the weight ratio of Maxmi:Minmi:Min is L:M:N:P, and the total amount is regenerated sand G% of the weight of the powder; the weight ratio of Maxmi:Minmi:Min is L:M:N:P, and the total amount is H% of the weight of the recycled sand powder; the weight ratio of Maxmi:Minmi:Min is L:M:N:P, and the total amount is I% of the weight of the recycled sand powder; the weight ratio of Maxmi:Minmi:Min is L:M:N:P, and the total amount is J% of the weight of the recycled sand powder; the weight ratio of Maxmi:Minmi:Min is L:M:N:P, and the total amount is K% of the weight of the recycled sand powder; prepare test blocks and measure the 7d strength;

[0038] S5-5. Based on the strength test results and the principle of low activator dosage and high test block strength, select several ratios with optimal performance.

[0039] Preferably, in step three, the activator is a composition of sodium sulfate, sodium silicate, sodium carbonate and sodium hydroxide, and sodium hydroxide, sodium carbonate, sodium silicate and sodium sulfate are added to a beaker in sequence, and sodium hydroxide, sodium carbonate, sodium silicate and sodium sulfate are stacked in sequence from bottom to top at the bottom of the beaker.

[0040] Preferably, in step five, water is added until the material just sticks to the inner walls around the stirring pot without falling off, and then the water is stopped, stirring is continued for 5 seconds, and then the stirring is stopped, and the slurry on the inner wall of the pot and the stirring blades is scraped off, and then the slurry is quickly stirred for 5 seconds before pouring.

[0041] The second aspect of the present invention provides a regenerated mortar, which is prepared by the above-mentioned regenerated mortar preparation method and includes the following components in parts by weight: 100 parts of cement, 400 parts of regenerated sand powder, 102-112 parts of water, and 4-40 parts of activator; the activator includes 0-25.45 parts of sodium sulfate, 0-16 parts of sodium silicate, 0-4 parts of sodium carbonate, and 0-2.15 parts of sodium hydroxide.

[0042] Preferably, the weight percentage of the activator to the regenerated sand powder is 1% to 10%, and in the activator, the ratio of sodium sulfate: sodium silicate: sodium carbonate: sodium hydroxide is 7:4:0:0 or 7:0:1:0 or 7:4:1:0 or 7:4:1:1.

[0043] Preferably, the cement is 42.5 grade ordinary Portland cement.

[0044] Preferably, the regenerated sand powder is a mixture of 0-9.5 mm sand and powder remaining after the waste concrete is crushed and screened by a jaw crusher to preferably obtain coarse aggregate, wherein the sand powder with particle sizes of 0-0.075 mm, 0.075-0.15 mm, 0.15-0.3 mm, 0.3-0.6 mm, 0.6-1.18 mm, 1.18-2.36 mm, 2.36-4.75 mm, and 4.75-9.5 mm accounts for 3.1%, 3.5%, 6.8%, 10.7%, 8.1%, 15.5%, 25.6%, and 26.7%, respectively.

[0045] Preferably, the sodium sulfate, sodium silicate and sodium hydroxide are solid particles, the sodium carbonate is solid powder, the sodium hydroxide is of premium grade, and the sodium sulfate, sodium silicate and sodium carbonate are of analytical grade.

[0046] A third aspect of the present invention provides a method for recycling regenerated mortar, comprising the following steps:

[0047] T1. Use a jaw crusher to crush the cast and hardened recycled mortar, and use a test sieve to confirm that all of it is crushed to less than 9.5 mm to obtain recycled sand powder;

[0048] T2. Prepare regenerated mortar using the method according to claim 1;

[0049] T3. When the recycled mortar after casting expires or needs to be demolished and rebuilt, repeat steps T1 and T2 until the recycled sand powder is recycled five times.

[0050] The unhydrated cement particles in the regenerated sand powder are wrapped by cement hydrates, containing a large amount of silicon and aluminum components. After high-temperature rapid cooling, they become active waste slag. The essence of the activity of waste slag is that the industrial raw materials are rapidly cooled after high temperature, and there is no time to convert them into stable compounds. The activity of the compounds is sealed in the form of vitreous and chemical energy. Acidic and alkaline substances are used as activators to dissolve the vitreous body, so that active silicon oxide and aluminum oxide are dissolved; cement hydration produces Ca(OH) 2 , activated silicon oxide, activated aluminum oxide, Ca(OH) 2 Dissolved in water to react and generate hydrated calcium silicate gel, turning the loose particles into a strong integral material. Sodium silicate and sodium carbonate are strong base and weak acid salts, which are alkaline in water and can dissolve cement hydrates that wrap unhydrated cement particles; sodium hydroxide is an alkali and can also dissolve the active silicon and aluminum components in the regenerated sand powder; sodium sulfate is a strong base and strong acid salt, which is neutral in water, but can react with calcium hydroxide produced by cement hydration to generate sodium hydroxide and calcium sulfate precipitation. The alkalinity of sodium hydroxide is stronger than that of calcium hydroxide produced by cement hydration, and its dissolution effect on regenerated sand powder is greater than that of cement; at the same time, sodium silicate reacts with calcium hydroxide to generate sodium hydroxide and calcium silicate, and sodium carbonate reacts with calcium hydroxide to generate sodium hydroxide and calcium carbonate, that is, sodium sulfate, sodium silicate, and sodium carbonate can consume the calcium hydroxide produced by cement hydration, which can accelerate cement hydration. Under the conditions of 20% cement and 80% regenerated sand powder, the early strength of regenerated mortar can be improved. Substances dissolve in water with heat absorption and release, and there are many substances that release heat when dissolved, such as sodium hydroxide and sodium carbonate. There are relatively few substances that absorb heat when dissolved, except for ammonium nitrate and sodium sulfate. The substances that absorb heat and release heat when dissolved are the most numerous, and most of the substances that dissolve in water in life belong to this category, such as sucrose. The dissolution of sodium silicate is best completed at a higher concentration, that is, the amount of water used during dissolution is low; and the higher the concentration of NaOH in the solution, the easier it is to dissolve sodium silicate. On the one hand, NaOH can inhibit the occurrence of the hydrolysis process of sodium silicate and avoid the formation of Si0 2 Precipitation, on the other hand, makes free Si0 2 The peptization process is easy to carry out, which is beneficial to dissolution.

[0051] As described above, the present invention has the following beneficial effects:

[0052] (1) In the preparation method of the regenerated mortar of the present invention, the optimal dosage of the activator when added alone is cleverly used as the compounding ratio, which can quickly obtain the optimal ratio of the activator, which is equivalent to the traditional test method, and the test time is shortened from three months to one month.

[0053] (2) In the preparation method of the regenerated mortar of the present invention, the fluidity is controlled instead of the water-cement ratio. The slurry is observed to adhere to the inner wall of the mixing pot without falling off by naked eye. The regenerated mortar prepared by this method has higher strength than the regenerated mortar prepared by controlling the water-cement ratio, and it saves manpower and time, and reduces the amount of sewage disposal in the concrete mixing station.

[0054] (3) In the recycling method of the regenerated mortar of the present invention, the regenerated mortar is completely crushed into regenerated sand powder with a particle size of less than 9.5 mm and directly used for the next regenerated mortar preparation, and this cycle is repeated five times, thereby avoiding multiple screening and separate utilization of construction waste regenerated aggregate and regenerated powder, thereby improving work efficiency. Moreover, the regenerated sand powder is recycled five times, without the need for ball milling and calcination, saving five times of coal-fired energy consumption and electricity consumption, and the strength of the prepared mortar is as high as about 15.9-24.2MPa, which has great economic value.

[0055] (4) The dissolution time of sodium sulfate, sodium silicate, sodium carbonate and sodium hydroxide stacked in a beaker from top to bottom is shorter than that of reverse stacking, and dissolution by adding water in batches is 2 to 8 minutes faster than dissolution by adding water once, and the dissolution efficiency is high; the dissolution time of the activator is ≤2min and the compressive strength of the regenerated mortar is ≥15.5MPa, 18.3MPa, 20.4MPa, 21.4MPa and 21.9MPa respectively when the activator dosage is 0.1%, 1%, 4%, 7% and 10%.

[0056] (5) The activator in the present invention does not require thermal activation, and cleverly utilizes both endothermic and exothermic activators, thereby avoiding the problem that endothermic activators require a heat source to dissolve and thus waste resources, and also avoiding the problem that exothermic activators easily accelerate cement hydration and thus shorten construction time.

[0057] (6) The present invention crushes all the recycled mortar into recycled sand powder and directly uses it in the next cycle, avoiding multiple screening and separate utilization of recycled aggregate and recycled powder of construction waste, thereby improving work efficiency. The recycled sand powder can be recycled five times, without ball milling and calcination, saving five times of coal burning energy and electricity consumption, and the strength of the prepared mortar is as high as about 15.9-24.2MPa, which has great economic value.

[0058] (7) The present invention solves the problem of the mutual constraints among the stimulant's large enhancement effect, fast dissolution and low dosage. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] Figure 1 This is a graph of comparative example 6 verifying that the mortar slurry sticks to the inner wall of the mixing pot and does not fall off, and the time variation of the jumping table expansion degree.

[0060] Figure 2 This is a comparison of the appearance of the regenerated mortar of comparative example 7 and the regenerated mortar of embodiment 2.

[0061] Figure 3 It is a curve diagram of the assessment index of the regenerated mortar and a scatter diagram of the relationship between the activator dosage and strength of all the formulas in Example 1. DETAILED DESCRIPTION

[0062] The following is a description of the implementation of the present invention by means of specific embodiments. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification.

[0063] The purpose of the present invention is to study and develop a regenerated mortar with fast proportioning, promoted dissolution, capable of quickly and massively assessing strength data, low cycle energy consumption, high strength and stability, and a method for obtaining, preparing, assessing and recycling the proportioning of the regenerated mortar. The following Example 1 and Comparative Examples 1 to 3 illustrate the method for obtaining the proportioning of the regenerated mortar, Example 2 and Comparative Examples 4 to 6 illustrate the method for preparing the regenerated mortar, Example 3 and Comparative Example 8 illustrate the method for assessing the regenerated mortar, Example 4 and Comparative Examples 9 to 10 illustrate the method for recycling the regenerated mortar, and Example 5 and Comparative Example 11 illustrate the proportioning of the regenerated mortar.

[0064] In the present invention, unless otherwise specified, cement was purchased from Taicang Conch Cement Plant and was P.O42.5 ordinary Portland cement; regenerated sand powder was purchased from Shanghai Youhong Environmental Protection Technology Co., Ltd. and obtained through a crushing and screening process, with a particle size of 0-9.5 mm; in the activator, sodium silicate was purchased from Shanghai Shisi Hewei Chemical Co., Ltd. and had a molecular formula of Na 2 SiO 3 9H 2 O, analytically pure, colorless orthorhombic bipyramidal crystals, Na 2 O content 19.3w / %-22.8w / %, Na 2 O and SiO 2 The molar ratio is 1.00-1.06, chloride (Cl) ≤ 0.01w / %, aluminum (Al) ≤ 0.05w / %, iron (Fe) ≤ 0.05w / %, heavy metal (in terms of Pb) ≤ 0.001w / %; sodium sulfate was purchased from Sinopharm Chemical Reagent Co., Ltd., with the molecular formula of Na 2 SO 4 , analytically pure, colorless and transparent crystalline particles, content ≥99.0%, chloride (Cl) ≤0.001w / %, iron (Fe) ≤0.002w / %, heavy metal (in terms of Pb) ≤0.005w / %; sodium carbonate was purchased from Tianjin Zhiyuan Chemical Reagent Co., Ltd., with a molecular formula of Na 2 CO 3 , analytically pure, white powder, content (Na 2 CO 3)≥99.8%, chloride (Cl)≤0.002w / %, iron (Fe)≤0.0005w / %, heavy metal (as Pb)≤0.0005w / %; sodium hydroxide was purchased from Tianjin Hengxing Chemical Reagent Manufacturing Co., Ltd., with the molecular formula of NaOH, high-grade purity, and white crystalline particles, with a content (NaOH)≥98.0%, chloride (Cl)≤0.02w / %, aluminum (Al)≤0.001w / %, iron (Fe)≤0.005w / %, and heavy metal (as Pb)≤0.001w / %; water was tap water.

[0065] The compressive strength of the recycled mortar is tested according to GB / T17671-1999 "Test method for strength of cement mortar (ISO method)"; the expansion of the recycled mortar is tested according to GB / T2419-2005 "Test method for fluidity of cement mortar".

[0066] Example 1

[0067] This embodiment provides a method for obtaining a proportion of regenerated mortar, comprising the following steps:

[0068] S1. Determine that the weight percentage of the regenerated sand powder in (regenerated sand powder + cement) is 70%-100%, and the weight percentage of the activator in the regenerated sand powder is 0%-10%.

[0069] S2. Prepare test blocks according to the weight percentage of recycled sand powder in (recycled sand powder + cement) of 70%, 80%, 90% and 100%, respectively, and measure the 7d strength. According to the strength measurement results, the optimal weight percentage of recycled sand powder is 80%.

[0070] S3. Based on the weight percentage of regenerated sand powder in (regenerated sand powder + cement) being 80%, the weight ratios of sodium sulfate, sodium silicate, sodium carbonate and sodium hydroxide to regenerated sand powder are designed to be 0.1%, 1% and 10% respectively. Test blocks are prepared and the 7d strength is measured. According to the measurement results, the optimal dosage of sodium sulfate is 1% to 10% of the weight of regenerated sand powder, the optimal dosage of sodium silicate is 1% to 10% of the weight of regenerated sand powder, the optimal dosage of sodium carbonate is 1% to 10% of the weight of regenerated sand powder, and the optimal dosage of sodium hydroxide is 0.1% to 1% of the weight of regenerated sand powder. The activator enhancement effect is ranked as follows: sodium sulfate>sodium silicate>sodium carbonate>sodium hydroxide.

[0071] S4. Based on the weight percentage of regenerated sand powder (regenerated sand powder + cement) of 80%, the weight ratios of sodium sulfate, sodium silicate, sodium carbonate and regenerated sand powder are designed to be 4% and 7% respectively. The sodium hydroxide dosage in the range of 0-10% of the weight of the regenerated sand powder has no obvious reinforcing effect on the regenerated mortar, so this test can be omitted. Prepare test blocks and measure the 7d strength. According to the measurement results, the optimal dosage of the activator when added alone is determined to be 7% of the weight of the regenerated sand powder, 4% of the weight of the regenerated sand powder, 1% of the weight of the regenerated sand powder, and 1% of the weight of the regenerated sand powder.

[0072] S5. In order to compare with the single-addition activator, a composite admixture test was conducted based on the proportion of recycled sand powder to (recycled sand powder + cement) of 80%, as follows:

[0073] S5-1. Design a double-doping test of sodium sulfate and sodium silicate; the weight ratio of sodium sulfate to sodium silicate is 1:1; the total doping amount is 7% of the weight of the regenerated sand powder; the weight ratio of sodium sulfate to sodium silicate is 1:1, and the total doping amount is 4% of the weight of the regenerated sand powder; the weight ratio of sodium sulfate to sodium silicate is 7:4, and the total doping amount is 7% of the weight of the regenerated sand powder; the weight ratio of sodium sulfate to sodium silicate is 7:4, and the total doping amount is 4% of the weight of the regenerated sand powder; the weight ratio of sodium sulfate to sodium silicate is 7:4, and the total doping amount is 1% of the weight of the regenerated sand powder; the weight ratio of sodium sulfate to sodium silicate is 7:4, and the total doping amount is 10% of the weight of the regenerated sand powder; prepare test blocks and measure the 7d strength.

[0074] S5-2. Design a test for dual-doping of sodium sulfate and sodium carbonate; the weight ratio of sodium sulfate to sodium carbonate is 1:1; the total doping amount is 7% of the weight of regenerated sand powder; the weight ratio of sodium sulfate to sodium carbonate is 1:1; the total doping amount is 1% of the weight of regenerated sand powder; the weight ratio of sodium sulfate to sodium carbonate is 7:1; the total doping amount is 7% of the weight of regenerated sand powder; the weight ratio of sodium sulfate to sodium carbonate is 7:1; the total doping amount is 1% of the weight of regenerated sand powder; prepare test blocks and measure the 7d strength.

[0075] S5-3. Design a three-mix test of sodium sulfate, sodium silicate and sodium carbonate; the weight ratio of sodium sulfate, sodium silicate and sodium carbonate is 1:1:1, and the total mixing amount is 7% of the weight of the regenerated sand powder; the weight ratio of sodium sulfate, sodium silicate and sodium carbonate is 1:1:1, and the total mixing amount is 4% of the weight of the regenerated sand powder; the weight ratio of sodium sulfate, sodium silicate and sodium carbonate is 1:1:1, and the total mixing amount is 1% of the weight of the regenerated sand powder; The weight ratio is 7:4:1, and the total amount is 7% of the weight of the regenerated sand powder; the weight ratio of sodium sulfate, sodium silicate and sodium carbonate is 7:4:1, and the total amount is 4% of the weight of the regenerated sand powder; the weight ratio of sodium sulfate, sodium silicate and sodium carbonate is 7:4:1, and the total amount is 1% of the weight of the regenerated sand powder; the weight ratio of sodium sulfate, sodium silicate and sodium carbonate is 7:4:1, and the total amount is 10% of the weight of the regenerated sand powder; prepare test blocks and measure the 7d strength.

[0076] S5-4. Design a test of compounding four activators; the weight ratio of sodium sulfate, sodium silicate, sodium carbonate and sodium hydroxide is 1:1:1:1, and the total dosage is 7%; the weight ratio of sodium sulfate, sodium silicate, sodium carbonate and sodium hydroxide is 1:1:1:1, and the total dosage is 4% of the weight of the regenerated sand powder; the weight ratio of sodium sulfate, sodium silicate, sodium carbonate and sodium hydroxide is 1:1:1:1, and the total dosage is 1% of the weight of the regenerated sand powder; the weight ratio of sodium sulfate, sodium silicate, sodium carbonate and sodium hydroxide is 7:4 :1:1, the total amount accounts for 7% of the weight of the regenerated sand powder; the weight ratio of sodium sulfate, sodium silicate, sodium carbonate and sodium hydroxide is 7:4:1:1, and the total amount is 4% of the weight of the regenerated sand powder; the weight ratio of sodium sulfate, sodium silicate, sodium carbonate and sodium hydroxide is 7:4:1:1, and the total amount is 1% of the weight of the regenerated sand powder; the weight ratio of sodium sulfate, sodium silicate, sodium carbonate and sodium hydroxide is 7:4:1:1, and the total amount is 10% of the weight of the regenerated sand powder; prepare test blocks and measure the 7d strength.

[0077] S5-5 Based on the test results, assessment indicators and the principle of low activator dosage and high strength, 15 formulations with the best performance were selected, namely: (1) sodium sulfate, the dosage is 7% of the weight of the regenerated sand powder; (2) sodium sulfate and sodium silicate are compounded in a weight ratio of 7:4, the dosage is 7% of the weight of the regenerated sand powder; (3) sodium sulfate, the dosage is 4% of the weight of the regenerated sand powder; (4) sodium sulfate and sodium carbonate are compounded in a weight ratio of 7:1, the dosage is 7% of the weight of the regenerated sand powder; (5) sodium sulfate and sodium silicate are compounded in a weight ratio of 7:4, the dosage is 10% of the weight of the regenerated sand powder; (6) sodium sulfate, sodium silicate and sodium carbonate are compounded in a weight ratio of 7:4:1, the dosage is 4% of the weight of the regenerated sand powder; (7) sodium silicate, the dosage is 4% of the weight of the regenerated sand powder; (8) Sodium carbonate, the amount of which is 1% of the weight of the regenerated sand powder; (9) Sodium sulfate, sodium silicate, sodium carbonate and sodium hydroxide are mixed in a weight ratio of 7:4:1:1, and the amount of which is 7% of the weight of the regenerated sand powder; (10) Sodium sulfate and sodium silicate are mixed in a weight ratio of 7:4:1, and the amount of which is 4% of the weight of the regenerated sand powder; (11) Sodium sulfate and sodium carbonate are mixed in a weight ratio of 7:1, and the amount of which is 1% of the weight of the regenerated sand powder; (12) Sodium silicate, the amount of which is 1% of the weight of the regenerated sand powder; (13) Sodium sulfate, the amount of which is 1% of the weight of the regenerated sand powder; (14) Sodium sulfate, sodium silicate, sodium carbonate and sodium hydroxide are mixed in a weight ratio of 1:1:1:1, and the amount of which is 7% of the weight of the regenerated sand powder; (15) Sodium silicate, the amount of which is 0.1% of the weight of the regenerated sand powder.

[0078] In the above steps, the fluidity is controlled to be constant by adjusting the amount of water used when preparing the regenerated mortar.

[0079] The test data of the embodiment are shown in Table 1. In Table 1, H represents sodium hydroxide, C represents sodium carbonate, S represents sodium sulfate, and Si represents sodium silicate.

[0080] Table 1

[0081]

[0082] As shown in Table 1, the optimal dosage of each activator when added alone is 7% sodium sulfate, 4% sodium silicate, 1% sodium carbonate, and 1% sodium hydroxide (the mass percentage here refers to the weight percentage of the regenerated sand powder). The proportion of the activators is consistent when mixed, and the strength of the total activator dosage of 7%> the strength of the total activator dosage of 4%> the strength of the total activator dosage of 1%. Specifically: S Si CH 7 / 4 / 1 / 17% strength 20.6MPa (indicates that the weight ratio of sodium sulfate, sodium silicate, sodium carbonate, and sodium hydroxide is 7:4:1:1, the total dosage is 7% of the weight of the regenerated sand powder, and the 7d compressive strength of the obtained test block is 20.6MPa, and the following expressions are similar), S SiC H 7 / 4 / 1 / 14% strength 18.8MPa, S Si CH 7 / 4 / 1 / 1 1% strength 17.0MPa. S Si C 7 / 4 / 1 7% strength 21.7MPa, S Si C 7 / 4 / 1 4% strength 21.7MPa, S Si C 7 / 4 / 1 1% strength 16.3MPa. SC 7 / 1 7% strength 22.4MPa, SC 7 / 1 1% strength 19.9MPa. S Si 7 / 4 7% strength 24.2MPa, S Si 7 / 4 4% strength 20.4MPa, S Si 7 / 4 1% strength 17.3MPa.

[0083] When the total amount of the activator is constant during the composite doping, the activator is used as the optimal doping amount when it is single doped as a proportion, and the strength is higher than that of the equal proportion. Specifically: S Si CH 7 / 4 / 1 / 1 7% strength is 20.6MPa, S Si CH 1 / 1 / 1 / 1 7% strength is 18.6MPa. SSi C 7 / 4 / 1 7% strength is 21.7MPa, S Si C 1 / 1 / 1 7% strength is 17.3MPa. SC 7 / 1 7% strength is 22.4MPa, SC 1 / 1 7% strength is 16.8MPa. S Si 7 / 4 7% strength is 24.2MPa, S Si 1 / 1 7% strength is 21.4MPa. This shows that when the strength is highest (i.e. when the doping amount is 7%), the strength is greater with the optimal doping amount as the proportion relative to the equal proportion, i.e. S Si C H7 / 4 / 1 / 1 is stronger than 1 / 1 / 1 / 1, S Si C 7 / 4 / 1 is stronger than 1 / 1 / 1, S Si 7 / 4 is stronger than 1 / 1, and SC 7 / 1 is stronger than 1 / 1.

[0084] Although the total doping amount is the same at 7%, S Si 7 / 0 is stronger than 7 / 4, but S Si 7 / 0 needs 5 minutes to dissolve, which is inefficient, while SSi 7 / 4 only needs 2 minutes to dissolve. The activators have a dissolution-promoting effect.

[0085] Comparative Example 1

[0086] This comparative example is basically the same as Example 1. The differences are: 1. The "7d strength" in all steps is changed to "28d strength". 2. In S2, the activators sodium sulfate, sodium silicate, sodium carbonate, and sodium hydroxide are added in an amount of 0.04% by weight of the regenerated sand powder, 0.07% by weight of the regenerated sand powder, 0.4% by weight of the regenerated sand powder, 0.7% by weight of the regenerated sand powder, 4% by weight of the regenerated sand powder, and 7% by weight of the regenerated sand powder, respectively. 3. S4 is deleted.

[0087] The test results of Comparative Example 1 are shown in Table 2.

[0088] Combining Table 1 and Table 2, it can be seen that the 28-day strength of Comparative Example 1 is basically consistent with the 7-day strength of Example 1, which indicates that in order to shorten the test period in the method for obtaining the proportion of regenerated mortar, the traditional strength test can be adjusted from 28 days to 7 days.

[0089] Comparative Example 1 tests the strength for 28 days and the single-mixing formula is completed in one go. Example 1 tests the strength for 7 days and the single-mixing formula is done twice. The first time, the optimal dosage range of each stimulant is determined to be 0-0.1%, 0.1%-1%, or 1%-10%. The second time, the dosage of each stimulant is designed to be 0.04%, 0.07%, or 0.4%, 0.7%, or 4%, 7%. Example 1 can do 18 fewer pots of tests. Each pot of test requires purchasing raw materials, preparing reimbursement vouchers, weighing materials, making mixtures, adjusting water consumption, molding, testing strength, cleaning the laboratory, recording test data, and uploading test photos. The 18 fewer pots of tests are conducive to improving the enthusiasm of technical personnel for research and development, improving product performance by adjusting the ratio, and are low in cost, high in efficiency, and save human resources compared to the transformation of equipment and processes. Similarly, 13 formulations with the largest activator were obtained. It took 84 days to make 61 pots of mortar in Comparative Example 1, and it took 28 days to make 43 pots of mortar in Example 1, which was nearly 2 months earlier than the optimal ratio.

[0090] Table 2

[0091]

[0092] Comparative Example 2

[0093] This comparative example is basically the same as Example 1. The difference is that the compound formula "S Si 1 / 17%, S Si 1 / 1 4%, S Si 7 / 4 7%, S Si 7 / 4 4%, S Si 7 / 4 1%, S Si 7 / 4 10%, SC 1 / 17%, SC 1 / 1 1%, SC 7 / 1 7%, SC 7 / 1 1%, S Si C 1 / 1 / 1 7%, S Si C 1 / 1 / 1 4%, S Si C 1 / 1 / 1 1%, S Si C 7 / 4 / 1 7%, S Si C 7 / 4 / 1 4%, S Si C 7 / 4 / 1 1%, S Si C 7 / 4 / 1 10%, S Si CH 1 / 1 / 1 / 1 7%, S Si CH 1 / 1 / 1 / 1 4%, S Si CH 1 / 1 / 1 / 1 1%, S Si CH 7 / 4 / 1 / 1 7%, S Si CH 7 / 4 / 1 / 1 4%, S Si CH 7 / 4 / 1 / 1 1%, S Si C H7 / 4 / 1 / 1 10%" is replaced with "S Si 2 / 1 7%, S Si 3 / 1 7%, S SiC 2 / 2 / 1 7%, S Si C 2 / 1 / 1 7%, S Si CH 2 / 2 / 2 / 1 7%, S Si CH 2 / 2 / 1 / 1 7%”.

[0094] The test results of Comparative Example 2 are shown in Table 3.

[0095] Table 3

[0096] Example 1 Compounding Formula Example 1 Compressive strength / MPa Comparative Example 3 Compounding Formula Comparative Example 3 Compressive Strength / MPa S Si 7 / 4 7% 24.2 S Si 2 / 1 7% 18.2 S Si 3 / 1 7% 17.3 S Si C7 / 4 / 1 7% 21.7 S Si C 2 / 2 / 1 7% 17.5 S Si C 2 / 1 / 1 7% 15.7 S Si CH 7 / 4 / 1 / 1 7% 20.6 S Si CH 2 / 2 / 2 / 1 7% 18.3 S Si CH 2 / 2 / 1 / 1 7% 17.8

[0097] It can be seen from Table 3 that the recycled mortar compounding ratio is designed according to the conventional 1:2:3, and the strength is lower than that of Example 1 according to the optimal dosage of 7:4:1:1.

[0098] Comparative Example 3

[0099] This comparative example is basically the same as Example 1, except that: "In the above steps, the fluidity is controlled to be constant by adjusting the amount of water used when preparing the regenerated mortar" is changed to "In the above steps, the water-cement ratio is controlled to be constant when preparing the regenerated mortar." The compressive strength and required water-cement ratio of the regenerated mortar described in this comparative example are shown in Table 4.

[0100]

[0101] As shown in Table 4, the strength of the regenerated mortar prepared by fixing the water-binder ratio in Comparative Example 3 is lower than that of fixing the fluidity in Comparative Example 1. It can also be seen from Test No. 1 in Table 4 that the activator has the effect of reducing the water demand and improving the compressive strength of the regenerated mortar. Without adding the activator, the mortar containing 20% ​​cement and 80% regenerated sand powder requires a water-binder ratio of 1.20 and a compressive strength of 15.0 MPa. After adding the activator, the required water-binder ratio is reduced to 1.00-1.14, and the compressive strength is increased to 18.3-25.0 MPa.

[0102] Example 2

[0103] This embodiment provides a method for preparing regenerated mortar. The proportion of the regenerated mortar in this embodiment is as shown in test number 20 in Table 1. The preparation method comprises the following steps:

[0104] Step 1: Dry mix the powders: dry mix the cement and recycled sand powder in a mixing pot.

[0105] Step 2. The activators are stacked in order in the beaker: sodium hydroxide, sodium carbonate, sodium silicate, and sodium sulfate are added to the beaker in sequence, so that sodium hydroxide, sodium carbonate, sodium silicate, and sodium sulfate are stacked from bottom to top at the bottom of the beaker, that is, the stacking priority is: sodium hydroxide>sodium carbonate>sodium silicate>sodium sulfate.

[0106] Step 3. Dissolve the activator in batches: Keep the mortar stirring pot in a slow stirring state at all times, and add water to the beaker while stirring the activator with a glass rod. After the first dissolution, pour the supernatant into the stirring pot. Crush the precipitate in the beaker with the back of a spoon. If it cannot be crushed completely, take the precipitate to a piece of paper and crush it with the back of a spoon. After crushing, add water to the beaker again, stir to dissolve, pour the supernatant into the stirring pot, crush the precipitate and add water again, and repeat this process until the activator is completely dissolved. Add water to dissolve 3 times in total. For the last dissolution, rinse the beaker with water and pour the rinse water into the stirring pot.

[0107] Step 4: Adjust the amount of water: Add water until the material just sticks to the inner wall of the stirring pot without falling off, stop adding water, stir for 5 seconds, stop stirring, scrape off the slurry on the inner wall of the pot and the stirring blade, and stir quickly for 5 seconds. Pour into the test mold without vibration compaction, form, demould, and naturally cure.

[0108] The preparation method of the regenerated mortar in Example 1 is the same as the preparation method of this embodiment, except that if step 2 does not involve a certain activator, it is not added; if step 3 can be dissolved into a clear liquid in one time without precipitation, it does not need to be dissolved in batches; if it can be dissolved into a clear liquid in two times and the precipitation disappears, it only needs to be dissolved twice.

[0109] In this embodiment, the dissolution phenomenon of the activator is shown in Table 5.

[0110] Table 5

[0111]

[0112] As shown in Table 5, sodium hydroxide and sodium carbonate release heat when dissolved in water, sodium silicate does not change significantly when dissolved in water, and sodium sulfate absorbs heat when dissolved in water. Therefore, sodium sulfate becomes hard when it comes into contact with water, and is not easy to crush with the back of a spoon, and is not easy to melt; sodium silicate becomes hard when it comes into contact with water, but can be crushed and is easier to melt. This shows that one of the reasons why the co-doping of activators dissolves faster than the single doping is that the exothermic activator has a dissolution-promoting effect on the endothermic activator.

[0113] In this embodiment, the dissolution time of the stimulant is shown in Table 6.

[0114] Table 6

[0115]

[0116] As shown in Table 6, the multi-doped activator dissolves faster than the single-doped activator. When the single activator is added, sodium hydroxide and sodium carbonate dissolve instantly in water, while sodium sulfate and sodium silicate are more difficult to dissolve, especially at high concentrations. It takes 8 minutes to dissolve 10% sodium sulfate and 5 minutes to dissolve 10% sodium silicate. The formula of the multi-doped activator can be dissolved within 2 minutes.

[0117] The co-doping of sodium sulfate and sodium silicate dissolves faster than either of them alone. It takes 2 minutes for S Si 7 / 4 7% to dissolve, 5 minutes for S 7%, and 3 minutes for Si 7% to dissolve.

[0118] Sodium carbonate and sodium hydroxide promote the dissolution of sodium sulfate and sodium silicate. It takes 1 minute for S Si C 7 / 4 / 1 4% to dissolve, 3 minutes for S 4%, 2 minutes for Si 4%, and C 4% to dissolve instantly. It takes 1 minute for S Si CH 1 / 1 / 1 / 11% to dissolve, 2 minutes for S 1%, 1 minute for Si 1%, C 1% to dissolve instantly, and H 1% to dissolve instantly. The strength of the multi-doped activator is lower than that of the single-doped activator. The strength of S Si 7 / 4 7% is 24.2MPa, the strength of S 7% is 25MPa, and the strength of Si7% is 17.6MPa. The strength of S Si C 7 / 4 / 1 4% is 21.7MPa, the strength of S 4% is 23.4MPa, the strength of Si 4% is 21.1MPa, and the strength of C 4% is 16.5MPa. S Si CH 1 / 1 / 1 / 1 1% strength 18.3MPa, S 1% strength 19.1MPa, Si1% strength 19.4MPa, C 1% strength 20.6MPa, H 1% strength 16.3MPa.

[0119] The conventional conclusion is that the strength of the co-doped activator is higher than that of the single doped activator. This study achieved an unexpected effect. The strength of the co-doped activator is lower than that of the single doped activator, and the co-doped activator dissolves faster than the single doped activator.

[0120] Comparative Example 4

[0121] This comparative example is basically the same as Example 2. The difference is that in step 2, the stacking order of the activators at the bottom of the beaker is inverted, and the stacking priority order is changed from "sodium hydroxide>sodium carbonate>sodium silicate>sodium sulfate" to "sodium sulfate>sodium silicate>sodium carbonate>sodium hydroxide". The dissolution time of the inverted activators described in this comparative example is shown in Table 7.

[0122] Table 7

[0123]

[0124] As shown in Table 7, the dissolution time of S Si CH stacked from top to bottom in the beaker of Example 2 is 0-2 minutes, and the dissolution time of S Si CH stacked from bottom to top in the beaker of Comparative Example 4 is 4-8 minutes. This is because the sodium sulfate placed at the bottom of the beaker of Comparative Example 4 contacts water first when water is gradually added to the beaker, and immediately agglomerates, waiting for the sodium hydroxide on the top to dissolve and release heat when it contacts water, and it is too late to melt the sodium sulfate block, and the dissolution effect is not good. The sodium sulfate block needs to be crushed, water is added, and stirring is slow to dissolve. When water is gradually added to the beaker of Example 2, the sodium hydroxide placed at the bottom of the beaker contacts water first and releases heat when dissolving. When the sodium sulfate on the top contacts water, the water is already warm, and the sodium sulfate instantly dissolves in the warm water, achieving twice the result with half the effort.

[0125] Comparative Example 5

[0126] This comparative example is basically the same as Example 2, except that the multiple additions of water to dissolve the activator in step 3 are changed to one-time addition of water to dissolve the activator, that is, "the activator is dissolved once: while the mortar stirring pot is kept in a slow stirring state at all times, water is added to the beaker while stirring the activator with a glass rod. After dissolution, the activator aqueous solution is poured into the stirring pot. And the amount of water added at one time is equal to the total amount of water added in batches in Example 2." The time for the one-time addition of water to dissolve the activator described in this comparative example is shown in Table 8.

[0127] Table 8

[0128]

[0129] As shown in Table 8, the total amount of water used for dissolution is the same. In Example 2, water is added multiple times and stirred continuously, and it takes 0-2 minutes to dissolve the precipitate of the activator in the water. In Comparative Example 5, water is added only once and stirred continuously, and it takes 4-10 minutes to wait for the activator to be completely dissolved. It can be seen that the dissolution of Example 2 by adding water in batches is 2 to 8 minutes faster than the dissolution of Comparative Example 5 by adding water once, and the dissolution efficiency is high.

[0130] Comparative Example 6

[0131] The purpose of this comparative example is to verify whether the judgment method of stopping adding water in step 4 of Example 2, "adding water until the material just sticks to the inner wall around the stirring pot without falling off", can control the fluidity of the slurry to be consistent. The specific method is to use the water-binder ratio of Example 2 to test the mortar jumping table expansion.

[0132] The fluidity of the verification mortar described in this comparative example is shown in Table 9. The slurry of the verification mortar described in this comparative example adheres to the inner wall of the stirring pot without falling and the degree of expansion of the jumping table is shown in Table 9. Figure 1 shown.

[0133] Table 9

[0134]

[0135] Combined with Table 9, Figure 1 It can be seen that in Example 2, water is gradually added to the regenerated sand powder and cement. When the slurry just sticks to the inner wall of the stirring pot and does not fall, it is just when the fluidity is 175±5mm. It can be seen that the amount of water added is controlled by "the slurry just sticks to the inner wall of the stirring pot and does not fall", which is consistent with the amount of water used to adjust the mortar jump table expansion within the range of 175±5mm. However, in Example 6, the jump table expansion test is performed. Each molding test takes 2 minutes, waiting for the jump table to jump 25 times takes 35s, lifting the cone test mold to scrape off the inner wall slurry takes 10s, using a vernier caliper to test and record the mortar expansion takes 1 minute, pouring out the sample and cleaning the rag and wiping the cone test mold and the jump table takes 3 minutes, each time takes 6 minutes and 45 seconds, and 43 times (because 43 ratios are designed) take 290 minutes. In Example 2, water addition is stopped when the slurry just sticks to the inner wall of the mixing pot and does not fall off. While ensuring the same technical effect (controlling the expansion degree within the range of 175±5mm), manpower and time are saved and the amount of sewage disposal in the concrete mixing station is reduced.

[0136] Comparative Example 7

[0137] This comparative example is basically the same as Example 2, except that the "powder dry mixing: cement and regenerated sand powder are dry mixed in a stirring pot" in step one is changed to "cement, regenerated sand powder, and activator are dry mixed in a stirring pot", step two is deleted, and the dissolution of the activator in batches in step three is changed to "add water to the stirring pot and stir evenly".

[0138] The regenerated mortar in which the activator is not pre-dissolved in this comparative example and the regenerated mortar in which the activator is pre-dissolved in Example 2 are shown in FIG. Figure 2 shown.

[0139] Depend on Figure 2 It can be seen that in comparative example 7, the activator is not pre-dissolved, the activator is locally aggregated in the mortar, and dark patches appear. In example 2, the activator is pre-dissolved, the activator is evenly dispersed in the mortar, and the mortar has a uniform color.

[0140] Example 3

[0141] The present embodiment provides a method for assessing recycled mortar. The assessment indicators described in the present embodiment are: the activator dosage is 0.1%, 1%, 4%, 7%, and 10%, and the qualified compressive strength of the regenerated mortar is 15.5MPa, 18.3MPa, 20.4MPa, 21.4MPa, and 21.9MPa, respectively. The assessment method described in the present embodiment is that the mortar is qualified if the dissolution time is less than 2 minutes and the strength is higher than the assessment indicator. The assessment indicators of the recycled mortar described in this embodiment and the activator dosage-strength relationship of all the formulas in Example 1 are shown in FIG. Figure 3 shown.

[0142] Figure 3 The scattered points are the activator dosage-strength points of all the formulas in Example 1, and the lines are the connecting lines of the qualified compressive strength of the mortar at different activator dosages, i.e., the assessment index. Figure 3 It can be seen that half of the scattered points are above the line, which indicates that half of the formulas meet the assessment index, indicating that this assessment index is more appropriate.

[0143] Comparative Example 8

[0144] The difference between this comparative example and Example 3 is that this comparative example adopts the traditional assessment method to rank the 43 formulations in Example 1 (see Table 1) by strength.

[0145] The strength ranking of the 43 formulations in Example 1 described in this comparative example is shown in Table 10.

[0146] Table 10

[0147]

[0148] As can be seen from Table 10, using the traditional assessment method of Comparative Example 8, when the single dosage of sodium sulfate is 7% of the weight of the regenerated sand powder, the strength is 25MPa, which is the highest, but it takes 5 minutes to dissolve, which does not meet the requirement of the dissolution time of less than 2 minutes in the assessment method of Example 3. When the weight ratio of sodium sulfate and sodium silicate is 7:4 and the total dosage is 7% of the weight of the regenerated sand powder, the strength is 24.2MPa, which is relatively high, and it only takes 2 minutes to dissolve, which meets the requirement of the dissolution time of less than 2 minutes in the assessment method of Example 3, and is the optimal formula. When the dosage of sodium sulfate is 10% of the weight of the regenerated sand powder, the strength is 21.7MPa. According to the strength ranking table of Comparative Example 8, it is the formula with the seventh highest strength among the 43 formulas, but according to the assessment indicator of Example 3 "10% strength of stimulator>21.9MPa", it is judged as unqualified. Although the assessment indicators of Example 3 are not used, and the principle of low dosage and high strength is used, it can be judged that the strength is the same as 21.7MPa, and the S Si C 7 / 4 / 1 7% formula is better than the S10% formula because it saves more stimulants. However, the assessment indicators of Example 3 are more quantitative and objective, and are convenient for rapid and large-scale data analysis. The scattered points located above the line are qualified. It is possible that Formula 1 has low strength and low stimulant dosage, while Formula 2 has high strength and high stimulant dosage. At this time, it is impossible to simply compare and analyze the advantages and disadvantages of the two examples. However, through the assessment indicators in Example 3, by comparing the numerical values ​​of the assessment indicators of the two, the advantages and disadvantages of the comprehensive performance of the two can be quickly compared. For example, the strength of the formula S Si 1 / 1 4% of Test No. 21 in Example 1 is 19.4MPa, and the strength of the formula S Si 1 / 1 7% of Test No. 20 in Example 1 is 21.4MPa. It can be quickly judged that the formula S Si 1 / 1 4% Figure 2 The overall performance below the middle line is poor, formula S Si 1 / 1 7% Figure 2 Better above the center line.

[0149] Example 4

[0150] This embodiment provides a method for recycling recycled mortar. The raw material composition of the recycled mortar in this embodiment is the same as that of test number 22 in Example 1. The strength of the mortar made by recycling recycled sand powder in this embodiment is shown in Table 11. The method for recycling recycled mortar in this embodiment includes the following steps:

[0151] T1. Crush the regenerated mortar with a jaw crusher and use a test sieve to confirm that it is all crushed to less than 9.5 mm to obtain the regenerated sand powder for the second cycle.

[0152] T2. Use 20% cement, 80% recycled sand powder, 1.04 water-cement ratio and 7% activator S Si 7 / 4 to prepare recycled mortar.

[0153] T3. When the service life expires or needs to be demolished and rebuilt, repeat T1 and T2 until the regenerated sand powder is recycled five times.

[0154] Table 11

[0155]

[0156] As shown in Table 4, the strength of the regenerated mortar prepared by using the recycled sand powder for the first time is 24.2MPa. The strength of the regenerated mortar prepared by crushing all the regenerated mortar into the recycled sand powder and applying it to the formula again is 23.5MPa. Similarly, the strengths of the regenerated mortar prepared by using the recycled sand powder for the third, fourth and fifth cycles are 22.2MPa, 19.9MPa and 15.9MPa respectively. Crushing all the regenerated mortar into recycled sand powder and directly using it in the next cycle avoids multiple screening and separate use of the recycled aggregate and recycled powder of construction waste, thereby improving work efficiency.

[0157] Comparative Example 9

[0158] The difference between this comparative example and Example 4 is that step T1 is to crush the regenerated mortar with a jaw crusher, then grind it with a ball mill to less than 0.075 mm, and finally calcine it in a furnace at 1000 degrees Celsius for 3 hours to obtain recycled regenerated micropowder. The regenerated sand powder in T2 and T3 is replaced with regenerated micropowder. The strength of the net slurry prepared by the recycled calcined regenerated micropowder described in this comparative example is shown in Table 12.

[0159] Table 12

[0160]

[0161] It can be seen from Table 12 that all the regenerated mortar is crushed, ball-milled, and calcined into regenerated micropowder and directly used in the next cycle. Although the strength of the reused regenerated net slurry remains unchanged, the energy consumption of high-temperature calcination, ball milling and other processes is too high, and the micropowder lacks aggregates, so the strength of the regenerated net slurry is low, about 13.8 to 15.1 MPa. Example 4 does not require ball milling and calcination, and the strength is about 15.9-24.2 MPa. It is reported that the cement production is 1.231 billion tons, consuming 131 million tons of standard coal. Example 4 recycles the regenerated sand powder five times without calcination, saving a total of five times of coal burning energy consumption, which has great economic value.

[0162] Comparative Example 10

[0163] The difference between this comparative example and Example 4 is that step T1 is to crush the regenerated mortar with a jaw crusher, and then grind it with a ball mill to less than 0.075 mm to obtain recycled micro powder. In T2 and T3, the regenerated sand powder is replaced with regenerated micro powder.

[0164] The strength of the net slurry prepared by recycling the ball-milled regenerated micropowder described in this comparative example is shown in Table 13.

[0165] Table 13

[0166]

[0167] It can be seen from Table 13 that the recycled mortar is completely crushed and ball-milled into recycled micro-powder and directly used in the next cycle. Each time the recycled micro-powder is reused, it needs to be ball-milled, which consumes a lot of energy. In addition, the micro-powder is not calcined and lacks aggregate, resulting in low strength of the recycled net mortar.

[0168] Electricity consumption has always been a headache for construction waste treatment plants. In the process of construction waste treatment, ball mills consume the most electricity. Generally, the motor power is hundreds of kilowatts, and large-scale ball mills consume even more energy. Therefore, in the industrial production process, it is crucial to improve the strength of recycled building materials without reducing energy consumption. Example 4 Recycle the recycled sand powder five times without grinding, saving a total of five times of ball milling energy.

[0169] Example 5

[0170] This embodiment provides a regenerated mortar. The raw material composition and properties of the regenerated mortar in this embodiment are shown in Table 14; the preparation method of the regenerated mortar is shown in Example 2.

[0171] Table 14

[0172]

[0173] As shown in Table 14, the compressive strength of Examples 5-1 to 5-8 is 20.4 to 24.2 MPa, and the dissolution time of the activator is 0 to 2 min. Comparative Example of Example 5: Except for test numbers 6, 17, 22, 23, 24, 28, 34, and 40 in Table 1 of Example 1, the remaining proportions are the comparative examples of Example 5. As shown in Table 1, test number 1 is a blank control group without the addition of an activator, with 20% cement, 80% recycled sand powder, 1.20 water-binder ratio, and a compressive strength of 15.0 MPa.

[0174] The compressive strength of Examples 5-1 to 5-8 is 36%-61% higher than that of the blank control group. The compressive strength of the regenerated mortar in Test No. 4 is 11.4 MPa with a sodium hydroxide content of 10%, which is lower than that of the blank control group. It can be seen that inappropriate activator dosage will reduce the strength of the regenerated mortar.

[0175] The compressive strength of test numbers 2, 3, 7, 10, 15, 26, 32, and 35 is about 15-16 MPa, which is not higher than that of the blank control group. It can be seen that it is difficult to use the activator scheme to improve the strength of high-dosage recycled sand powder-based mortar, and it is not possible to successfully prepare it by simply trying a few ratios.

[0176] The compressive strength of test numbers 18, 19, 25, 27, 31, 37, 39, and 41 was about 17-18 MPa, which was not significantly improved compared with the blank control group.

[0177] The compressive strength of test numbers 8, 9, 14, 36, and 43 is about 19-22MPa, which is significantly improved compared with the blank control group, but the strength per unit dosage is low, which is lower than the assessment index requirements proposed in this patent: the strength of 7% activator dosage is ≥21.4MPa, and the strength of 10% activator dosage is ≥21.9MPa.

[0178] The activator dosage of test numbers 11, 16, 21, 29, and 38 is 1% to 4%, and the compressive strength is about 19 MPa. The activator dosage is low, but the compressive strength is not excellent enough.

[0179] The compressive strength of test numbers 20 and 33 is higher than 20MPa, which is also higher than the assessment index requirement proposed in this patent: the strength of 7% activator is ≥21.4MPa, but is lower than the strength of the same dosage of Examples 5-1 to 5-8.

[0180] The compressive strength of test numbers 12 and 13 is higher than 23MPa, but the dissolution time of the activator is 3 to 5min, which does not meet the assessment index requirement proposed in this patent: dissolution time ≤2min.

[0181] It can be seen from this that when the recycled sand powder dosage is as high as 80%, the activator has a large reinforcement effect but dissolves slowly and the dosage is high. Therefore, using a low-dosage activator to greatly improve the mortar strength while ensuring that the activator dissolves quickly requires overcoming the mutual constraints of the activator: large reinforcement effect, fast dissolution, and low dosage.

[0182] Comparative Example 11

[0183] The difference between this comparative example and Example 5-5 is that this comparative example does not add an activator, cement / (cement+regenerated sand powder)=60%, and regenerated sand powder / (cement+regenerated sand powder)=40%. The raw material composition and properties of the regenerated mortar described in this comparative example are shown in Table 15.

[0184] Table 15

[0185]

[0186] As can be seen from Table 15, the strength also reaches 21MPa. Comparative Example 11 does not use an activator, and only 40% of the regenerated sand powder can be added. Example 5-5 uses the activator formula of this patent, and the amount of regenerated sand powder added can be increased to 80%, which is doubled.

[0187] In summary, the present invention provides a method for obtaining, preparing, evaluating and recycling recycled mortar with dissolution-promoting, recycling, fast ratio, simple fluidity control, and rapid and large-scale analysis of the advantages and disadvantages of the formula, and a method for obtaining, preparing, evaluating and recycling the ratio of the recycled mortar. Based on its simple and efficient characteristics, it can promote the production of a large number of high-dosage solid waste-based inorganic finished product formulas. Compared with equipment and process improvements, formula optimization is the most labor-saving and cost-effective. In formula optimization, ratio design, trial fast preparation, performance testing, and index measurement require a lot of time and a lot of mental and physical labor, which often makes scientific researchers exhausted. The technical solution of the present invention allows scientific researchers to easily obtain a series of optimal formulas and reduce the pressure on scientific researchers.

[0188] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A method for preparing regenerated mortar, characterized in that: The following steps are involved: Step 1: Determine the ratio of cement, recycled sand powder and activator in the recycled mortar, which specifically includes the following steps: S1. Preliminary determination of the weight percentage of regenerated sand powder: (regenerated sand powder + cement) is in the range of (A-30)% to A%, and the weight percentage of activator: regenerated sand powder is in the range of 0 to (B 100)%; S2. Select the weight percentage of regenerated sand powder: (regenerated sand powder + cement) is A%, (A-10)%, (A-20)%, (A-30)%, the amount of activator is 0, prepare test blocks, measure the 7d strength, and determine the weight percentage of regenerated sand powder: (regenerated sand powder + cement) is C% according to the measurement results, C=A or (A-10) or (A-20) or (A-30); S3. Based on C%, the activators sodium sulfate, sodium silicate, sodium carbonate and sodium hydroxide were tested respectively, with the weight percentage of activator: regenerated sand powder being B%, (B 10)%(B 100)%, respectively, prepare test blocks, measure the 7d strength, according to the measurement results, the four stimulants are ranked according to the excitation intensity, the stimulant with the highest excitation intensity is recorded as Max, the stimulant with the second highest excitation intensity is recorded as Maxmi, the stimulant with the second lowest excitation intensity is recorded as Minmi, and the stimulant with the lowest excitation intensity is recorded as Min. The best weight percentage of Max and regenerated sand powder is D%~E%, the best weight percentage of Maxmi and regenerated sand powder is F%~G%, the best weight percentage of Minmi and regenerated sand powder is H%~I%, and the best weight percentage of Min and regenerated sand powder is J%~K%. D%~E%, F%~G%, H%~I%, J%~K%=[0~B%] or [B%~(B 10)%] or [(B 10)%~(B 100)%]; S4, based on C%, the dosage of Max is (E / 10) of the weight of the regenerated sand powder 4%, weight of regenerated sand powder (E / 10) 7%, Maxmi dosage is the weight of regenerated sand powder (G / 10) 4%, weight of regenerated sand powder (G / 10) 7%, Minmi dosage is (I / 10) of the weight of regenerated sand powder 4%, weight of regenerated sand powder (I / 10) 7%, the minimum dosage is the weight of the regenerated sand powder (K / 10) 4%, weight of regenerated sand powder (K / 10) 7%, test blocks were prepared respectively, and the 7d strength was measured. According to the strength measurement results, the optimal dosages of Max, Maxmi, Minmi and Min when mixed alone were selected, which were L%, M%, N% and P% of the weight of the recycled sand powder respectively. S5. Based on C%, conduct a compounding test on Max, Maxmi, Minmi, and Min; specifically: S5-1. Conduct a composite admixture test on Max and Maxmi; according to the weight ratio of Max:Maxmi being 1:1, the total admixture is L% of the weight of the regenerated sand powder; the weight ratio of Max:Maxmi being 1:1, the total admixture is M% of the weight of the regenerated sand powder; the weight ratio of Max:Maxmi being L:M, the total admixture is L% of the weight of the regenerated sand powder; the weight ratio of Max:Maxmi being L / M, the total admixture is M% of the weight of the regenerated sand powder; the weight ratio of Max:Maxmi being L:M, the total admixture is D% of the weight of the regenerated sand powder; the weight ratio of Max:Maxmi being L:M, the total admixture is E% of the weight of the regenerated sand powder; the weight ratio of Max:Maxmi being L:M, the total admixture is F% of the weight of the regenerated sand powder; the weight ratio of Max:Maxmi being L:M, the total admixture is G% of the weight of the regenerated sand powder; prepare test blocks and measure the 7d strength; S5-2. Conduct a composite admixture test on Max and Minmi; according to the weight ratio of Max:Minmi being 1:1, the total admixture is L% of the weight of the regenerated sand powder; the weight ratio of Max:Minmi being 1:1, the total admixture is N% of the weight of the regenerated sand powder; the weight ratio of Max:Minmi being L:N, the total admixture is L% of the weight of the regenerated sand powder; the weight ratio of Max:Minmi being L:N, the total admixture is N% of the weight of the regenerated sand powder; prepare test blocks and measure the 7d strength; S5-3. Test the compounding of Max, Maxmi and Minmi; according to the weight ratio of Max:Maxmi:Minmi being 1:1:1, the total compounding amount is L% of the weight of the regenerated sand powder; the weight ratio of Max:Maxmi:Minmi being 1:1:1, the total compounding amount is M% of the weight of the regenerated sand powder; the weight ratio of Max:Maxmi:Minmi being 1:1:1, the total compounding amount is N% of the weight of the regenerated sand powder; the weight ratio of Max:Maxmi:Minmi being L:M:N, the total compounding amount is L% of the weight of the regenerated sand powder; the weight ratio of Max:Maxmi:Minmi being L:M:N, the total compounding amount is M% of the weight of the regenerated sand powder; the weight ratio of Max:Maxmi:Minmi being L:M:N, the total compounding amount is N% of the weight of the regenerated sand powder; the weight ratio of Max:Maxmi:Minmi is L:M:N, and the total amount is D% of the weight of the regenerated sand powder; the weight ratio of Max:Maxmi:Minmi is L:M:N, and the total amount is E% of the weight of the regenerated sand powder; the weight ratio of Max:Maxmi:Minmi is L:M:N, and the total amount is F% of the weight of the regenerated sand powder; the weight ratio of Max:Maxmi:Minmi is L:M:N, and the total amount is G% of the weight of the regenerated sand powder; the weight ratio of Max:Maxmi:Minmi is L:M:N, and the total amount is H% of the weight of the regenerated sand powder; the weight ratio of Max:Maxmi:Minmi is L:M:N, and the total amount is 1% of the weight of the regenerated sand powder; prepare test blocks and measure the 7d strength; S5-4. Conduct a composite admixture test on Max, Maxmi, Minmi, and Min; according to the weight ratio of Max:Maxmi:Minmi:Min of 1:1:1:1, the total admixture is L% of the weight of the regenerated sand powder; the weight ratio of Max:Maxmi:Minmi:Min is 1:1:1:1, and the total admixture is M% of the weight of the regenerated sand powder; the weight ratio of Max:Maxmi:Minmi:Min is 1:1:1:1, and the total admixture is N% of the weight of the regenerated sand powder; the weight ratio of Max:Maxmi:Minmi:Min is 1:1:1:1, the total admixture is P% of the weight of the recycled sand powder; the weight ratio of Max:Maxmi:Minmi:Min is L:M:N:P, and the total admixture is L% of the weight of the recycled sand powder; the weight ratio of Max:Maxmi:Minmi:Min is L:M:N:P, and the total admixture is M% of the weight of the recycled sand powder; the weight ratio of Max:Maxmi:Minmi:Min is L:M:N:P, and the total admixture is N% of the weight of the recycled sand powder; the weight ratio of Max:Maxmi:Minmi:Min is L:M:N:P, and the total admixture is It is P% of the weight of the recycled sand powder; the weight ratio of Max:Maxmi:Minmi:Min is L:M:N;P, and the total addition amount is D% of the weight of the recycled sand powder; the weight ratio of Max:Maxmi:Minmi:Min is L:M:N:P, and the total addition amount is E% of the weight of the recycled sand powder; the weight ratio of Max:Maxmi:Minmi:Min is L:M:N:P, and the total addition amount is F% of the weight of the recycled sand powder; the weight ratio of Max:Maxmi:Minmi:Min is L:M:N:P, and the total addition amount is G% of the weight of the recycled sand powder. The weight ratio of Max:Maxmi:Minmi:Min is L:M:N:P, and the total amount is H% of the weight of the regenerated sand powder; the weight ratio of Max:Maxmi:Minmi:Min is L:M:N:P, and the total amount is 1% of the weight of the regenerated sand powder; the weight ratio of Max:Maxmi:Minmi:Min is L:M:N:P, and the total amount is J% of the weight of the regenerated sand powder; the weight ratio of Max:Maxmi:Minmi:Min is L:M:N:P, and the total amount is K% of the weight of the regenerated sand powder; prepare test blocks and measure the 7d strength; S5-5. According to the strength test results and the principle of low activator dosage and high test block strength, select several ratios with the best performance; Step 2: dry mix cement and recycled sand powder in a mixing pot according to the proportion in step 1; Step 3: According to the ratio in step 1, the stimulators are stacked in layers in a beaker according to their types; the stimulator is a combination of sodium sulfate, sodium silicate, sodium carbonate, and sodium hydroxide, and sodium hydroxide, sodium carbonate, sodium silicate, and sodium sulfate are added to the beaker in sequence, and sodium hydroxide, sodium carbonate, sodium silicate, and sodium sulfate are stacked in sequence from bottom to top at the bottom of the beaker; Step 4: While the stirring pot is in a slow stirring state, add water to the beaker and stir with a glass rod at the same time. After the first dissolution, pour the supernatant into the stirring pot, crush the precipitate in the beaker, add water to the beaker again and stir with a glass rod at the same time. After dissolution, pour the supernatant into the stirring pot, and repeat the cycle until the activator is completely dissolved; Step 5: Add water to the mixing pot until the material sticks to the inner wall around the mixing pot and does not fall off, pour it into a test mold, let it stand for forming, demoulding, and natural curing.

2. The method for preparing a regenerated mortar according to claim 1, characterized in that: In the step 5, add water until the material just sticks to the inner wall around the stirring pot without falling off, stop adding water, stir for 5 seconds, stop stirring, scrape off the slurry on the inner wall of the pot and the stirring blades, stir quickly for 5 seconds, and then pour.

3. A regenerated mortar, characterized in that: The regenerated mortar is prepared by the preparation method of any one of claims 1 to 2.

4. The regenerated mortar according to claim 3, characterized in that: The cement is 42.5 grade ordinary Portland cement.

5. The regenerated mortar according to claim 3, characterized in that: The regenerated sand powder is a mixture of 0-9.5 mm sand and powder remaining after the waste concrete is crushed and screened with a jaw crusher to obtain coarse aggregate, wherein the sand powder with particle sizes of 0-0.075 mm, 0.075-0.15 mm, 0.15-0.3 mm, 0.3-0.6 mm, 0.6-1.18 mm, 1.18-2.36 mm, 2.36-4.75 mm, and 4.75-9.5 mm account for 3.1%, 3.5%, 6.8%, 10.7%, 8.1%, 15.5%, 25.6%, and 26.7%, respectively.

6. The regenerated mortar according to claim 3, characterized in that: The sodium sulfate, sodium silicate and sodium hydroxide are solid particles, the sodium carbonate is solid powder, the sodium hydroxide is of premium grade, and the sodium sulfate, sodium silicate and sodium carbonate are of analytical grade.

7. A method for recycling recycled mortar, characterized in that: The following steps are involved: T1. Use a jaw crusher to crush the cast and hardened recycled mortar, and use a test sieve to confirm that all of it is crushed to less than 9.5 mm to obtain recycled sand powder; T2. Prepare regenerated mortar using the method according to claim 1; T3. When the recycled mortar after casting expires or needs to be demolished and rebuilt, repeat steps T1 and T2 until the recycled sand powder is recycled five times.

Citation Information

Patent Citations

  • Low-energy environment-friendly type building slag reclaimed sand powder mixed material and preparation method thereof

    CN103253882A

  • Alkali slag concrete composite activator and preparation method of concrete mixture

    CN106045361A

  • Method for preparing lightweight high-strength cast-in-place concrete partition wall by using building waste

    CN108395276A

  • Cement-based marine soft soil curing agent based on industrial waste and composite activator

    CN110563424A

  • Building spoil compound material for 3D printing as well as preparation method and application thereof

    CN111138135A